1987
DOI: 10.3109/00498258709167410
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity and metabolism of the pyrethroidscis-andtrans-cypermethrin in rainbow trout,Salmo gairdneri

Abstract: 1. The toxicity of cis- and trans-cypermethrin to rainbow trout was investigated and the concentrations of the two isomers in brain associated with toxic signs (excitability and loss of equilibrium) were determined. cis-Cypermethrin and trans-cypermethrin were equally toxic and showed similar brain levels associated with toxic signs (cis:0.25 micrograms/g, mean (range 0.07-0.53); trans:0.17 micrograms/g (0.07-0.31]. 2. Orally administered cypermethrin was less toxic than predicted, probably due to poor intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
2
20
1
1
Order By: Relevance
“…Because they are highly lipophilic (attracted to the non-water soluble components of cells), pyrethroids are likely to be strongly absorbed by the gills, even from water containing low levels of pyrethroids (Smith and Stratton, 1986). Edwards et al (1986) reported acute toxicity symptoms of cypermethrin in rainbow trout such as, gill flailing, hyperactivity, loss of buoyancy and inability to remain upright.…”
Section: Discussionmentioning
confidence: 99%
“…Because they are highly lipophilic (attracted to the non-water soluble components of cells), pyrethroids are likely to be strongly absorbed by the gills, even from water containing low levels of pyrethroids (Smith and Stratton, 1986). Edwards et al (1986) reported acute toxicity symptoms of cypermethrin in rainbow trout such as, gill flailing, hyperactivity, loss of buoyancy and inability to remain upright.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, after dosing, the BCYP rapidly centralized in stomach, quickly transferred to intestine then partly or mostly were eliminated. Studies [16,36,37] in the fish, mammals, and birds have shown that the metabolites of CYP include DCVA and PBA. Sampling the last three points' sand, the DCVA and PBA were detected (Fig.…”
Section: Degradation Studiesmentioning
confidence: 99%
“…The experiment results show that ionic bonded CSP is more efficient than covalent bonded CSP. Edwards et al (Edwards et al, 1987) separated 3 pair out of the 4 pair enantiomers of the cypermethrin by using cellulose derivative chiral stationary phase with hexane and isopropanol used as the mobile phase, and the two enantiomers of the alpha-cypermethrin were also well separated. Schurig et al (Schurig et al, 1996) partly separated the two enantiomers of alphacypermethrin on cyclodextrins chiral stationary phase by using methanol / water as mobile phase.…”
Section: Methods Of Chiral Liquid Chromatographic Separation Of Pyrethmentioning
confidence: 99%
“…4 showed, 8 isomers of cypermethrin and cyfluthrin were separated, and the separation method was used to analysis the isomers of cypermethrin in pork samples The following Table 2 is made for the summary. (Maguire, 1990) cypermethrin Daicel chiracel OD 6 peaks (Edwards et al, 1997) cypermethrin Glycine Derivative I~II 8 peaks (Naobumi et al, 1990 ) phenothrin 10% QF-1 Sumipax OA-2000 6peaks (Doi et al, 1985) deltamethrin RP-8/Lichrosorb Si-60 1 peaks (Mourot et al, 1979) cypermethrin Pirkle type Amino column 5 peaks cyfluthrin Dupont zorbax 5 peaks (Tephem et al, 1990) cypermethrin Sumichiral OA-2500-I, Chirex DOG-3019-DO 4 peaks cis-permethrin, transpermethrin Sumichiral OA-2500-I each 2 peaks fenvalerate Pirkle I-A 4peaks (Cayley & Simpson, 1986) fenvalerate Brush-type chiral stationary phase 4peaks (Lee et al, 1987) permethrin Brush-type ligand exchange chiral stationary phase 4peaks (Dondi et al, 1999) tetramethrin OA-4700 pirkle column and -cyclodextrin 4peaks (Deng, 2004) prallethrin, Bioallethrin, prallethrin, cyphenothrin Cellulose each 2peaks (Xu, 2003) cis-bifenthrin (BF),permethrin (PM) Sumichiral OA-2500-I BF-2peaks, PM-2peaks cypermethrin、cyfluthrin Chirex 00G-3019-OD column 8 peaks (Mancini et al, 2004) fenpropathrin,beta-cypermethrin Chiralcel CD each 2 peaks S, R-bioallethrin -cyclodextrin as chiral additive, C8 column 2 peaks cis-cypermethrin ,trans-cypermethrin Cellulose-tris(3,5-dimethylphenylcarbamate) each 2peaks (Wang, 2006) cypermethrin Supelcosil LC-CN column coupled with Chiralcel OD-H 7 peaks (Ta et al, 2006) cis-cypermethrin Chiralcel CD column 2 peaks (Edwards et al, 1987 ) bifenthrin and fenpropathrin…”
Section: Methods Of Chiral Liquid Chromatographic Separation Of Pyrethmentioning
confidence: 99%